The Value of Marketing Tools in Arts Marketing - CHEN, Feiran (2007)
Nowadays the arts are becoming more and more recognized as being an intrinsic part of everyday human life. The arts industry has recognized the importance of studying how to market effectively. As commercial marketing cannot be simply transplanted into an arts environment, arts marketing is a specific area. The marketing strategy of various arts organizations has become particularly significant in the increasingly competitive arts environment. The focus on arts marketing is being encouraged to ensure the arts organizations long-term viability, profitability and sustainability.